2004
DOI: 10.1158/0008-5472.can-03-2382
|View full text |Cite
|
Sign up to set email alerts
|

A Single Treatment of Yttrium-90-labeled CHX-A″–C6.5 Diabody Inhibits the Growth of Established Human Tumor Xenografts in Immunodeficient Mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 25 publications
3
44
1
Order By: Relevance
“…Affibody ABY-002 radiolabeled with 111 In for SPECT as well as with 68 Ga for PET was shown to specifically target HER2-expressing xenografts in vivo with both isotopes, but the pharmacokinetic profile for 68 Ga-radiolabeled ABY-002 was favored (20). Both tracers were investigated further in BC patients (22); the findings were in agreement with the preclinical data.…”
Section: Preclinical Settingsupporting
confidence: 72%
See 2 more Smart Citations
“…Affibody ABY-002 radiolabeled with 111 In for SPECT as well as with 68 Ga for PET was shown to specifically target HER2-expressing xenografts in vivo with both isotopes, but the pharmacokinetic profile for 68 Ga-radiolabeled ABY-002 was favored (20). Both tracers were investigated further in BC patients (22); the findings were in agreement with the preclinical data.…”
Section: Preclinical Settingsupporting
confidence: 72%
“…In contrast, its bioengineered derived fragments [Fab fragments, F(ab9) 2 ] and variants (scFv, diabodies, and minibodies) and nontraditional protein scaffolds (Affibody molecules, Nanobodies, and anticalins) result in faster pharmacokinetics with similar affinity and specificity (9). These low-molecular-weight probes can be radiolabeled with isotopes-such as 68 Ga, 18 F, 64 Cu, and 76 Br for PET imaging-that have a short halflife, allowing imaging on the day of injection with a low radiation burden. In contrast, when mAbs are radiolabeled with isotopes that have a longer half-life-such as 89 Zr, 124 I, and 86 Y for PET imaging and 111 In for SPECT imaging-images can be retrieved up to several days after tracer injection, allowing optimal uptake in tumor tissue.…”
Section: Imaging Of Her2 (Target) Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a large portion of the radionuclide is filtered through the kidneys, it is important to carefully assess the potential for renal toxicity. Severe renal toxicity associated with directly radiolabeled FabV (31) and diabodies (32) has been reported in mice but there is a considerably higher retention of these agents in the kidneys than that seen with 90 Ybiotin or 90 Y-peptide. There has been an extensive examination of renal toxicity associated with the use of radiolabeled somatostatin receptor peptides in rats and humans (33,34), which suggested that renal toxicity requires several months to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Among the approaches taken are pretargeting methods (49), the use of genetically engineered immunoconstructs with molecular mass intermediate between that of intact immunoglobulin G and FabV fragments (50,51), and combination of radioimmunotherapy with other therapeutic modalities such as external beam irradiation or chemotherapy (52 -54). Chelated radiometals represent an alternate source of residualizing labels available for radioimmunotherapy, remaining trapped in lysosomes in the form of lysine adducts of the respective metal chelates (55).…”
Section: Discussionmentioning
confidence: 99%